Demolishing the Myth of the Default Human That Is Killing Black Mothers - Stephanie R. M. Bray; Monica R. McLemore (Frontiers Media S.A., 2021)
It took a white police officer's knee on George Floyd's neck before white people began to reckon with 400 years of slavery and its aftermath, the effects of which Black people have endured for generations. Monuments are being taken down, flags are being redesigned, and institutions that honored those who denied the humanity of Black people are being renamed. Unfortunately for Sandra Bland, Breonna Taylor, Sha-Asia Washington and countless other Black transgender people including those with capacity for pregnancy, there was no justice even prior to the global pandemic of SARS-Cov-2 or coronavirus; namely racism, violence, and the Black Maternal Health crisis that makes it less likely that Black women will survive pregnancy and childbirth. The purpose of this article is to situate the state of Black people with the capacity for pregnancy in the context of these existing crises to illuminate the myths that racism has perpetuated through science, health services provision and policy. The greatest of these is the myth of a default human that can serve as a standard for the rest of the population. This racist ideal underpins education, provision of care, research, policies, and public health praxis. Demolishing the myth starts with acknowledging that Black people are not the architects of their own destruction: the default standard of whiteness is. The article begins with a historical background on how this myth came to be and elucidates the development and perpetuations of the myth of the default human. Next, we present an evidence based scoping review of the literature to summarize current thinking with specific focus on the Black maternal health crisis, we make policy recommendations and retrofits of upstream public health approaches for existing programs toward health equity. We also situate Black maternal health as part of a reproductive justice frame that centers Black women and birthing people's autonomy and agency. In other words, we use the scoping review to end with reimagining public health policy and provide an actionable roadmap to specifically disrupt the myth of the default human and dismantle racism in education, provision of care, research, policies, and public health praxis.